2011
DOI: 10.1111/j.1567-1364.2010.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Some biological features of Candida albicans mutants for genes coding fungal proteins containing the CFEM domain

Abstract: Several biological features of Candida albicans genes (PGA10, RBT5 and CSA1) coding for putative polypeptide species belonging to a subset of fungal proteins containing an eight-cysteine domain referred as common in several fungal extracellular membrane (CFEM) are described. The deletion of these genes resulted in a cascade of pleiotropic effects. Thus, mutant strains exhibited higher cell surface hydrophobicity levels and an increased ability to bind to inert or biological substrates. Confocal scanning laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 63 publications
2
33
0
Order By: Relevance
“…Csa1 localizes in the hyphal wall (67,71) and was previously shown to be upregulated by Bcr1 (20). Consistent with our results, Perez et al (72,73) showed a decrease in the thickness of biofilms formed by an a/␣ CSA1 deletion mutant. Although Csa2 does not contain a GPI anchor, it has been shown to be an extracellular protein (74).…”
Section: Discussionsupporting
confidence: 81%
“…Csa1 localizes in the hyphal wall (67,71) and was previously shown to be upregulated by Bcr1 (20). Consistent with our results, Perez et al (72,73) showed a decrease in the thickness of biofilms formed by an a/␣ CSA1 deletion mutant. Although Csa2 does not contain a GPI anchor, it has been shown to be an extracellular protein (74).…”
Section: Discussionsupporting
confidence: 81%
“…In some species (such as the plant pathogen Magnaporthe grisea), CFEM members are involved in pathogenesis (47). In C. albicans, the CFEM family is associated with adhesion and biofilm formation (62) and in acquisition of iron from heme (82,83). Levels of Pga10 and Rbt5 in the cell wall are increased when oxygen is limited (72).…”
Section: Discussionmentioning
confidence: 99%
“…We also observed significant increases in expression of three related cell wall genes (RBT5, PGA7, and PGA10) (see Table S2 in the supplemental material). These each contain an 8-cysteine domain, belong to the family CFEM (common in several fungal extracellular membranes), and are associated with biofilm development and heme binding (62,82).…”
Section: Induction Of Gene Expression By Hypoxiamentioning
confidence: 99%
“…Cells grown at 42°C for 18 h showed a severe cell separation defect. Similarly, cell aggregates were also described for several mutants that show a defective wall, like the glycosylation mutant mnn9, pmt1, and pmt4 strains, the wall protein ecm33, pga10, and pga13 mutants, and the wall-associated transglycosylase bgl2 mutants (48,(63)(64)(65)(66). Gregori et al assigned the cell separation defect in caspofungin-treated cells to an increased expression of adhesins, mainly Als1 (67).…”
Section: Discussionmentioning
confidence: 99%